Potensi karbon aktif limbah kulit salak sebagai biosorben minyak jelantah - Sudarsih, Astutik Retno (Maliki Interdisciplinary Journal, 2024)
Used cooking oil (used cooking oil) is oil whose quality has declined as a result of prolonged use. The attributes in question include water content, colour, odour, and others such as free fatty acid content, peroxide number, safonification number, iodine number, and others. Daily use of cooking oil results in significant waste production and increases the risk of environmental harm. Salak fruit, on the other hand, is a fruit that grows all year round in Indonesia and is extremely common. Salak fruit is only ever utilised as fruit; the peel and seeds are hardly ever used. Further investigation reveals that salak skin debris can be used as activated carbon to clean used cooking oil and lessen the likelihood of environmental harm. According to the research, used cooking oil can have 66.35% fewer peroxides when salak skin waste is added.